Pembuatan Profile Kampung Mojo RW 10 Kota Surabaya - Rezzylina Dwi Akhirulyati; Muhammad Yasin (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
A village profile is needed to provide an accurate, comprehensive and integral picture of the village's potential and level of development. Through the University's Real Work Lecture activities on August 17 1945, we tried to help Kalidami RW 10 Village located in Surabaya City, East Java Province in an effort to create a village profile. Based on problem identification, the profile of Mojo RW 10 Village contains some information on the number of existing UMKM. However, there is some data that is still not complete or updated. For example, data that has not been updated is about Waste Generation, Village Profile, Waste Savings, etc. Therefore, the objectives of this service activity are: 1) creating a profile of Mojo RW 10 Village which contains complete village potential data and 2) presenting profile data of Mojo RW 10 Village which can be accessed in printed and electronic versions. The methods used are secondary data collection, surveys and interviews. Evaluation of this activity is carried out directly during the profile creation activity, so that output can be produced that meets the wishes of the target audience. The output of this activity is a printed book on the profile of Mojo RW 10 Village which is one of the documents available at the RW 10 hall and a video profile of Mojo RW 10 Village which has been uploaded on social media.